(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The importance of industrial practice in the formation of professional skills of students of pedagogical colleges is reflected in the formation of a new modern economic thinking, fostering entrepreneurship, efficiency, increasing the competence of workers, equipping them with methods of economic and system analysis, and the ability to competently apply them in everyday practice.